Police Performance in Countering Narcotics Problems - Wardana, Bagus Dwi Gangga; Siregar, Taufik; Pinem, Serimin (Journal La Sociale, 2025)
Countering narcotics crimes is one of the major challenges faced by the police, especially the Medan Police, considering the complexity of this crime which has an impact on various aspects of people's lives. This study aims to analyze the legal rules that underlie police performance, the role of the police in overcoming narcotics crimes, and the obstacles faced in the process. The research method used is a quantitative approach with data collection techniques through questionnaires, observations, and document studies. The sample consisted of Medan Police personnel and the local community. The results of the study show that the legal rules that underlie the role of the police, such as Law Number 35 of 2009 concerning Narcotics and the Regulation of the National Police Chief Number 14 of 2012, have provided a strong foundation in the implementation of their duties. The role of the police includes law enforcement, prevention through education, and rehabilitation for victims of narcotics abuse. However, the police face obstacles in the form of limited human resources, increasingly complex modus operandi of perpetrators, lack of community cooperation, and limited budget. These results show the importance of increasing police capacity through technology training, more adequate budget allocation, and active community involvement in narcotics control efforts. Collaboration between the police, government, and the community is needed to create a safer and drug-free environment, especially in the Medan area.